The List - VH1 (Firm). (New York Pocket Books, 2000)
"The definitive collection of pop music top-ten lists--inspired by the popular VH1 series"--P. [4] of cover.
Ever since VH1's The List started recruiting celebrities for on-air debates over everything from the Greatest Male Rock Star to the Most Overrated Song, people everywhere have been demanding their own vote. Now, in this addictive and conversation-sparking book of lists, the general populace has spoken. Here are some of the results, in more than 70 categories of great import, including:

-Artist You Most Want to Spend the Night With
-Sexiest Teen Idol
-Rock's Most Significant Moment
-Best Album
-Best TV Theme Song
-Most Fashionable Artist
-Best Lead Guitarist
-Best Music Video

Featuring celebrity lists from the likes of James Brown, Melissa Etheridge, Stewart Copeland of the Police, and Gavin Rossdale of Bush, celebrity quotes, a "Just Missed" section, and space at the back of the book for your own write-in lists, VH1 : THE LIST is a fun, interactive book--perfect for the opinionated pop-culture enthusiast in all of us.
Donated by Ms. Triccie Cantero, U.P. Samaskom 84.1.
Keywords: Popular music -- Miscellanea; Rock music -- Miscellanea